2014
DOI: 10.1099/ijs.0.061945-0
|View full text |Cite
|
Sign up to set email alerts
|

Parafilimonas terrae gen. nov., sp. nov., isolated from greenhouse soil

Abstract: A Gram-stain-negative, short rod-shaped, non-flagellated, yellow bacterium, designated strain 5GHs7-2 T , was isolated from a greenhouse soil sample in South Korea. 16S rRNA gene sequence analysis of strain 5GHs7-2 T indicated that the isolate belonged to the family Chitinophagaceae, and exhibited the highest sequence similarities with members of the genera Terrimonas (89.2-92.6 %), Sediminibacterium (90.8-91.4 %) and Chitinophaga (89.2-91.7 %), Filimonas lacunae YT21 T (91.7 %), members of the genus Segetibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Moreover, the genus Sphingomonas has been widely reported to possess diverse metabolic capabilities towards organic xenobiotics (Marchal et al ., ). In addition, the genera Parafilimonas and Arachidicoccus which belonged to family Chitinophagaceae, a member of phylum Bacteroidetes , were identified recently (Kim et al ., ; Madhaiyan et al ., ). Therefore, these results showed that bacterial community identified in the study is quite similar to the previous publications (Marchal et al ., ; Lv et al ., ; Madhaiyan et al ., ; Sun et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the genus Sphingomonas has been widely reported to possess diverse metabolic capabilities towards organic xenobiotics (Marchal et al ., ). In addition, the genera Parafilimonas and Arachidicoccus which belonged to family Chitinophagaceae, a member of phylum Bacteroidetes , were identified recently (Kim et al ., ; Madhaiyan et al ., ). Therefore, these results showed that bacterial community identified in the study is quite similar to the previous publications (Marchal et al ., ; Lv et al ., ; Madhaiyan et al ., ; Sun et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The description is as before (Kim S.-J. et al, 2014) with the following modification. The G+C content of the type-strain genome is 39.6%, its approximate size 4.99 Mbp, its GenBank deposit SAMN05444277.…”
Section: Discussionmentioning
confidence: 99%
“…14, which was identified to be a significantly (p<0.05) changed OTU and had the biggest contribution to the whole community change (Fig. 5a) compared to other OTUs, was 82% similar to Parafilimonas terrae, who has the ability to utilize propionic acid (Kim et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%